2017
DOI: 10.1016/j.uclim.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Greenbelts do not reduce NO2 concentrations in near-road environments

Abstract: Trees are believed to improve air quality, thus providing an important ecosystem service for urban inhabitants. However, empirical evidence on the beneficial effects of urban vegetation on air quality at the local level and in boreal climatic regions is scarce. We studied the influence of greenbelt-type forest patches on NO 2 levels (i) in front of, (ii) inside and (iii) behind greenbelts next to major roads in the Helsinki Metropolitan Area, Finland, during summer and winter using passive collectors. Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
(81 reference statements)
0
16
0
3
Order By: Relevance
“…These concentrations could be due to a relatively low height of HCB (<1m) that is insufficient to create a barrier effect. Similarly, past investigations have reported mixed results of pollutant concentrations behind trees that emerged from a lack of barrier effect at breathing height and lower density (Brantley et al, 2014;Chen et al, 2016;Hagler et al, 2012;Viippola et al, 2018;Yli-Pelkonen et al, 2017). In addition, major reasons for higher pollutant concentrations behind trees (TCB; single tree row) compared with TIB (multiple tree rows, up to 4) was due to the difference in thickness of tree rows and lower canopy to ground distance.…”
Section: Overall Pollutant Concentration Changes With Different Gimentioning
confidence: 95%
See 1 more Smart Citation
“…These concentrations could be due to a relatively low height of HCB (<1m) that is insufficient to create a barrier effect. Similarly, past investigations have reported mixed results of pollutant concentrations behind trees that emerged from a lack of barrier effect at breathing height and lower density (Brantley et al, 2014;Chen et al, 2016;Hagler et al, 2012;Viippola et al, 2018;Yli-Pelkonen et al, 2017). In addition, major reasons for higher pollutant concentrations behind trees (TCB; single tree row) compared with TIB (multiple tree rows, up to 4) was due to the difference in thickness of tree rows and lower canopy to ground distance.…”
Section: Overall Pollutant Concentration Changes With Different Gimentioning
confidence: 95%
“…The literature reports varying level of differences in pollutant concentration depending on the GI type (Abhijith et al, 2017;Chen et al, 2015;Hagler et al, 2012). For example, some studies showed decreased concentrations due to hedges (Tiwary et al 2008;Al-Dabbous and Kumar, 2014) whereas others showed that trees can result in both air quality deterioration (Tong et al, 2015;Morakinyo et al, 2016;Yli-Pelkonen et al, 2017 ) and improvement (Yin et al, 2011;Lin et al, 2016). Before drawing generalisations on the air quality benefits of GI, it is important to consider the type of pollutants evaluated and reflected in any associated guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan pilihan pilihan tanaman yang tepat dan luasan areal tertentu akan mampu menurunkan polusi suatu industri (1,12,13) . Beberapa kajian dengan lebar green belt mencapai 500 meter, Green belt mampu menurunkan polusi udara suatu kawasan (24,25) , sebaliknya dengan lebar green belt yang terbatas, seperti ditepian jalan raya, upaya tersebut tidak maksimal menurunkan kandungan pencemaran udara ambien (26,27,28) .…”
Section: Manfaat Green Belt Industri Pupuk Kieunclassified
“…Dengan alasan tersebut, ada suatu kehawatiran, rencana pembangunan Green Belt dengan lebar 50 dan panjang 600 meter di rencana kawasan industri KIE (5) , tidak menghasilkan penurunan polusi udara yang signifikan (26,27,28) . Hanya saja, untuk rencana kawasan industri pupuk KIE, selain kualitas udara ambien eksisiting yang masih baik (4,5) , hasil simulasi model konsentrasi gas buang dari cerobong rencana industri pupuk KIE telah memenuhi ketentuan baku mutu (6) .…”
Section: Manfaat Green Belt Industri Pupuk Kieunclassified
See 1 more Smart Citation